Essential University Physics: Volume 1 (4th Edition)

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 14 - Exercises and Problems - Page 272: 69


The proof is below.

Work Step by Step

We know the following equation: $\frac{2L}{v}=mT$ Since $T=\frac{1}{f}$, it follows: $\frac{2L}{v}=\frac{m}{f} \\ L = \frac{mv}{2f}$ Recall, $v=\lambda f$. Thus: $ L = \frac{m\lambda f}{2f}=\frac{m \lambda}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.